INTERNATIONAL CONTACTS OF CZECHOSLOVAK NURSES, 1920-1938 - Zaoralová, Růžena; Kutnohorská, Jana; Mikšová, Zdeňka (Profese Online, 2015)
Background: The study has been inspired by the paper of Susan McGann who discusses the international courses organized in London in the 1920s and 1930s, in which nurses from Czechoslovakia regularly participated.Aim: Using the experiences of Czechoslovak nurses abroad from 1920-1938, to give evidence of the origins of some topical problems in present nursing (the transformation of education for paramedical staff, the question of nurse competencies).Methods: The paper is based on the content analysis of articles and short reports published in two main Czechoslovak professional journals of the period: Zprávy Československého červeného kříže (in total 204 issues from 1920-1936) and Československá nemocnice (in total 96 issues from 1931-1938).Results: Research has proved intensive foreign contacts of Czechoslovak nurses on several levels (international courses, conferences, meetings of the international nursing organizations, activities of foreign nurses in Czechoslovakia, translations of professional publications), supported by the Czechoslovak Red Cross, the League of Red Cross Societies, the American Red Cross and the Rockefeller Foundation. Even when the first nursing school in Prague was established according to principles used at the school in Vienna and even when Czechoslovak nurses kept personal and correspondence contacts with colleagues from different countries of the world during the whole searched period, the orientation to the Anglo-American milieu proved to be crucial for gaining new experience in the field of nursing. Particularly the courses organized at Bedford College and Royal College of Nursing in London were of special importance.Conclusions: The content analysis of proposed changes debated at the international nursing conferences of the inter-war period has proved to be inspiring for present discussions on the transformation of education for paramedical staff and on the question of nurse competencies.
Keywords: the transformation of education for paramedical staff; nurse competencies; foreign contacts; professional journals; Czechoslovakia; inter-war period